Neuroform EZ Stenting for Symptomatic Intracranial Artery Stenosis: 30 Days Outcomes in a High-Volume Stroke Center - Xu, Haowen; Quan, Tao; Zaidat, Osama O.; Chen, Dapu; Wang, Zibo; Yuan, Yongjie; Yan, Baojun; Lu, Hong; Guan, Sheng (Frontiers in Neurology, 2019)
Objective To test whether Neuroform EZ stent placement combined with the modified techniques in symptomatic severe intracranial stenosis (ICAS) would result in lower rates of peri-procedural complications of intracranial stenting. Methods We retrospectively reviewed the clinical data from consecutive 71 patients who underwent Neuroform EZ stent placement combined with the modified techniques for symptomatic severe ICAS at our institute between January 2016 and October 2017. Primary outcome was ipsi-lateral ischemic stroke, intra-cerebral hemorrhage, or death within 30 days after stenting. Secondary outcome was technical success. Results The technical success rate was 100%. The mean pre and post-stent stenoses were 84.2% ± 9.1% (median 85%, IQR75% to 90%) and 16.9% ± 10.2 % (median 15%, IQR 10% to 25%). The frequency of ipsi-lateral stroke, intra-cerebral hemorrhage, or death within 30 days 0%. Conclusions The combined use of Neuroform EZ stent placement and the modified techniques for symptomatic severe ICAS is technically feasible and safe, with very low peri-procedural complications. Further studies are required to assess the long-term results of this approach.